Surrealism - Waldberg, Patrick (London : Thames and Hudson, 1968)
Aragon, Louis ; Arp, Jean ; Breton, andré ; de Chirico, Giorgio ; Dali, Salvador ; Eluard, Paul ; Ernst, Max ; Miró, Joan ; Picabia, Francis ; Ray, Man ; Tanguy, Yves ; etc.
Engels
boek